The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/aje/kwm375
|View full text |Cite
|
Sign up to set email alerts
|

Time Lines of Infection and Disease in Human Influenza: A Review of Volunteer Challenge Studies

Abstract: The dynamics of viral shedding and symptoms following influenza virus infection are key factors when considering epidemic control measures. The authors reviewed published studies describing the course of influenza virus infection in placebo-treated and untreated volunteers challenged with wild-type influenza virus. A total of 56 different studies with 1,280 healthy participants were considered. Viral shedding increased sharply between 0.5 and 1 day after challenge and consistently peaked on day 2. The duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

75
842
11
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 966 publications
(974 citation statements)
references
References 108 publications
75
842
11
11
Order By: Relevance
“…What this study adds is the additional information of the comprehensive burden of all‐influenza cases in primary care, be they mild or more severe, not only by age, but also by type/subtype, over a long time period. It is interesting that the “typical” pattern of influenza B shows a substantially higher relative iMAARI attack rate among school‐age children5, 6, 7, 8, 9, 10, 11, 12, 13, 14 compared to that in age group 0‐4 (Figure 5, right panel), although in absolute terms the attack rate among 5‐ to 14‐year‐old children is comparable to that caused by A(H3N2). This striking characteristic of influenza B concurs with data from two serological studies, one from the Netherlands and one from Germany, which investigated the seroprevalence of antibodies against influenza virus types and subtypes by year of age among children 17, 18.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…What this study adds is the additional information of the comprehensive burden of all‐influenza cases in primary care, be they mild or more severe, not only by age, but also by type/subtype, over a long time period. It is interesting that the “typical” pattern of influenza B shows a substantially higher relative iMAARI attack rate among school‐age children5, 6, 7, 8, 9, 10, 11, 12, 13, 14 compared to that in age group 0‐4 (Figure 5, right panel), although in absolute terms the attack rate among 5‐ to 14‐year‐old children is comparable to that caused by A(H3N2). This striking characteristic of influenza B concurs with data from two serological studies, one from the Netherlands and one from Germany, which investigated the seroprevalence of antibodies against influenza virus types and subtypes by year of age among children 17, 18.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in the three seasons following the pandemic, influenza‐associated consultations by patients with ILI were estimated in a population‐based surveillance project in 13 US health jurisdictions as 0.7%, 0.2% and 1.1% 16. Given that only between 30% and 80% of all influenza cases manifest themselves as ILI5, 6, 7, 8 and in the same year influenza seasons may be quite different in different countries, the estimated 2.6%, 1.0% and 8.9% in our study lie in a comparable magnitude as the US data. We believe that our combination of surveillance (using ARI data) followed by modelling estimates the population impact of influenza more realistically than sentinel systems that use ILI data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient records with missing RT‐PCR results or no report of fever were excluded from analysis. Patients with specimens collected more than 5 days after onset were also excluded due to a loss of viral detectability after 5 days 7 , 8 …”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown controversial findings of clinical features in cases infected with A and B infections 21, 22, 23. In both paediatric and adult populations, patients with influenza B infection showed similar clinical features compared with influenza A 22, 24, 25, 26.…”
Section: Introductionmentioning
confidence: 99%